(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The article presents the results of a study on the study of the physical and chemical properties of circulating industrial waters and mechanical impurities of their composition. In order to reduce the hardness of circulating water, various reagents were used, i.e. a mixture of Na3PO4+sulfonal; Na2PO4; Na2PO4+sulfonal; Ca(ОН)2 are unsuitable for reducing the hardness of circulating waters (Fig. 3.3), because the reduction in water hardness is not achieved to the limit using these reagents. To reduce the hardness of circulating industrial waters, the optimal reagent is recommended.